EKSPRESI SEMIOTIK TOKOH LEGENDARIS DALAM HIKAYAT RAJE BEIKOR - NFN Sarman (﻿Kantor Bahasa Provinsi Bangka Belitung, 2013)
As one of the products of culture, oral literature has inntimate connection with the life of the communities whereoral literature existed, related to the society in the past, present, and future. The relationship can be seen throughvarious signs and symbols that appear. It’s interesting to study or explore the inter-sign relationship. Therefore,this paper examines how problems of semiotic expression legendary figure which appear in The Tale of RajeBeikor? This study aims to describe the form of the appearance of a legendary figure in the saga Raje Beikor. Byusing a qualitative descriptive method, this research goal is expected to be achieved. Based on the result of dataresearch analysis found some behaviors that imply the expression of semiotic figures depicting the life cycle ofliving things beginning with the birth, childhood to adulthood, until became a king to death. There are manylegends in the Bangka Belitung Islands who need more in-depth assessment both in terms of the semiotic andother fields of study.